Empowering Photovoltaics with Smart Light Management Technologies - Schuster, Christian Stefano; Crupi, Isodiana; Halme, Janne; Koc, Mehmet; Mendes, Manuel João; Peters, Ian Marius; Yerci, Selc¸Uk (Springer International Publishing, 2022)
The daily Sun supplies the continents of the Earth with four times more energy than humanity consumes in a year. This enormous potential of solar energy to generate clean energy is therefore driving great efforts to replace conventional and unsustainable fossil fuel consumption that damages our climate and our environment. Solar photovoltaic (PV) is emerging as the fastest growing renewable energy technology in the world, yet its share to the electricity production currently is less than 3%. While coal and gas remain key to electricity production, the climate crisis demands a fast transition to a carbon-neutral energy system. In the year 2019, the PV industry produced solar panels with a capacity of about 115 GW. To reach multi-TW levels by 2030, PV production capacity needs to scale at high rates, and continued innovation is necessary. One way to increase production is to reduce silicon wafer thickness, making more cells from the amount of silicon produced. Thinning the cell will not only allow making more of them in less time but will also reduce the cost for a module, and for the electricity it generates. A thinner absorber reduces the absorption of sunlight. To counter this loss, optical concepts are needed. In this chapter, we review the most promising approaches in photonics that have made physically thinner but optically thicker solar cells possible. By enabling thinner solar cells, photonic solutions offer the possibility of efficiency enhancements at lower costs. We will explain their applications, discuss their challenges and estimate their impact on energy yield. Finally, we outline how non-silicon thin-film PV is opening up a plethora of consumer-oriented applications. Since the higher flexibility/bendability of thinner cells broadens their applicability range, thin-film PV will empower our transition to a 100% green society in many aspects of our lives.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Dielectric structures; Diffractive structures; Flexible PV; Light-trapping; Photovoltaics; Plasmonics; Solar energy; Tandem solar cells; Thin-film PV